PENGARUH KEPEMIMPINAN SPIRITUAL KEPALA SEKOLAH, KEPUASAN KERJA, DAN MOTIVASI INTRINSIK TERHADAP KOMITMEN AFEKTIF GURU - Afrida, Nia; Zahriyanti, Zahriyanti; Siraj, Siraj (Universitas Indraprasta PGRI, 2025)
This study aims to: (1) examine the impact of spiritual leadership on teachers' affective commitment in middle schools in the Lut Tawar area, Central Aceh; (2) assess how spiritual leadership influences affective commitment with job satisfaction as a moderating variable; (3) analyze how spiritual leadership affects affective commitment with intrinsic motivation as a moderating variable; (4) evaluate the effect of job satisfaction on teachers' affective commitment; and (5) examine the effect of intrinsic motivation on teachers' affective commitment. The study uses a quantitative method, with a sample of 143 out of a population of 223. Data were collected through a Likert scale questionnaire, and analyzed using correlation, regression, and Moderated Regression Analysis (MRA). The findings show: 1) Spiritual leadership significantly affects teachers' affective commitment; 2) Spiritual leadership does not influence affective commitment through job satisfaction as a moderating variable; 3) Spiritual leadership does not affect affective commitment through intrinsic motivation as a moderating variable; 4) Intrinsic motivation has a significant effect on teachers' affective commitment.